The structure and the properties of dynamic thermoplastic elastomers based on polyethylene and ethylene-propylene-diene rubber - T. V. Zaderenko; R. G. Satvalov; V. D. Yulovskaya; O. A. Serenko (Тонкие химические технологии, 2013)
Composites based on LDPЕ, HDPЕ and oil-extended EPDM were investigated. It is shown that the matrix polymer predetermines the depth of completion of phase segregation and the structure of dynamic thermoplastics formed by reactionary blending during dynamic vulcanization of the thermoplastic-rubber blend